First case report of human myiasis with Sarcophaga species in Makkah city in the wound of a diabetic patient - Zaglool, Dina Abdulla Muhammad (Medknow Publications & Media Pvt Ltd, 2013)
We have reported a case of a 40-year-old male diabetic patient, resident of a rural area, who visited the outpatient clinic of the diabetic center in Alnoor Specialist Hospital, Makkah, Saudi Arabia. He came to seek medical advice for a single wound in the back of the shoulder since 1 month. After examination, a larva was eliminated and sent to laboratory for confirmation. It was confirmed as the third-stage larva of Sarcophaga species after macroscopic and microscopic examination. This is the first case of a patient having diabetic wound myiasis with the larva of Sarcophaga species reported in the Makkah region of Saudi Arabia.